Report of the Working Group on Monitoring and Evaluation of Tribal Development and Development of Backward Classes New Delhi July 1979 - Planning Commission (Planning Commission, 1980)
The 1978 report on Monitoring and Evaluation of Tribal Development and Development of Backward Classes, prepared by a Ministry of Home Affairs Working Group, addresses gaps in the implementation of development programs for Scheduled Tribes (STs) and Scheduled Castes (SCs). Despite substantial investments, disparities exist between policy intentions and outcomes, highlighting the need for an effective monitoring and evaluation system. The report recommends a structured, multi-level reporting framework encompassing ITDPs, state departments, and central ministries, supported by regular data collection, feedback mechanisms, and personnel training. By integrating continuous monitoring with data-informed decision-making, the report aims to enhance program effectiveness, ensure transparency in fund utilization, and bridge developmental gaps for tribal and backward class populations across India.
Government of India Ministry of Home Affairs
Government of India Ministry of Home Affairs
Keywords: Tribal Development; Backward Classes; Scheduled Tribes; Scheduled Castes; Monitoring System; Evaluation Framework; Integrated Tribal Development Projects; Implementation Gaps; Socioeconomic Programs; Data-Informed Decision Making